Increasing the Brand Awareness of the Square Surabaya Through Its Website - Kevin Merco (Institute of Research and Community Outreach - Petra Christian University, 2018)
The Square Surabaya is a hotel that was established in 2011, located at Jalan Siwalankerto No.146-148, Surabaya. The main problem The Square Surabaya is facing is the low awareness of their company.This problem led The Square Surabaya to have a low occupation rate problem. The main cause of this problem is the fact that their promotion tools, for example, their website, is out of date and ordinary without highlighting their unique selling points or showing their strength. Therefore, the adequate solution to The Square Surabaya’s problem is to improve their current website. The new website will enhance in terms of content and design. By having a good website, The Square Surabaya can have a good impression for the guest or the potential customer. The company canalsopromote more about their product togain potential customers. Lastly,by having this website, The Square Surabaya can promote their hotel betterusing their uniqueness and strength.